2014
DOI: 10.5539/jas.v6n4p68
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nutrient, Phytochemical and Antiradical Evaluation of 10 Amaranth (Amaranthus spp.) Varieties Before and After Flowering

Abstract: Amaranth (Amaranthus spp.) vegetable is widely consumed in Kenya and contributes to the alleviation of food insecurity. It is reported to have bioactive components such as antioxidants that help in protecting the body from long-term degenerative diseases. However, amaranth vegetable has also been shown to contain some anti-nutrients such as tannins, phytic acid, oxalates and nitrates which may bind nutrients and reduce their bioavailability in the body. There are many amaranth varieties and there is very littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…It was observed that scavenging activity was higher at site 2 than site 1 and the percentage inhibition showed the following trend Stage I >Stage III >Stage II. This outcome is also supported by Nyonje, (2014)38 who also reported that Stage II showed least percentage inhibition.…”
supporting
confidence: 69%
“…It was observed that scavenging activity was higher at site 2 than site 1 and the percentage inhibition showed the following trend Stage I >Stage III >Stage II. This outcome is also supported by Nyonje, (2014)38 who also reported that Stage II showed least percentage inhibition.…”
supporting
confidence: 69%
“…These results were consistent with a 2014 study from Kenya, which found pre-flowering values of beta-carotene in amaranth ranging from 39.1-47.8 mg/100 g fresh weight, and post-flowering values ranging from 41.2-47.3 mg/100 g fresh weight. 7 A second study from 2004 reported slightly higher, but similar levels of beta-carotene in fresh leaves. 6 In areas lacking vitamin A, magnesium, or copper, later harvest would be optimal.…”
Section: Discussionmentioning
confidence: 95%
“…6 One 2014 study found differences between pre-flowering and postflowering beta-carotene levels, so we anticipated that levels might also change during vegetative growth. 7 In this project, we aimed to detect differences across vegetative development when individuals are most likely to consume the leaves.…”
Section: Introductionmentioning
confidence: 99%
“…It is required for the maintenance of healthy skin, gums and blood vessels. It is also known to have many biological functions including collagen formation, absorption of inorganic iron, and it is an antioxidant, that reportedly reduces the risk of arteriosclerosis, cardiovascular diseases and some forms of cancers (Amanabo et al, 2011;Nyonje et al, 2014). Iron is a mineral found in every cell of the body.…”
Section: Introductionmentioning
confidence: 99%